Post-transplantation Presentation of ANCA-associated Vasculitis: Granulomatosis with Polyangitis - M A Shafiee; G Parastandechehr; S Tabatabavakili; M Shahroukh; A Haghighi; B Broumand (International Journal of Organ Transplantation Medicine, 2018)
Granulomatosis with polyangitis (GPA) is characterized by necrotizing granulomatosis of the upper and lower respiratory tract and glomerulonephritis. If GPA does not respond to appropriate management, it might result in end-stage renal disease, which may remit the disease severity. The overall impression is that immunosuppression following renal transplantation would further subside the vasculitis. However, several studies have shown that systemic vasculitis recur in 25% of patients following renal transplantation. This may indicate the perplexing nature of the immune system. One of the key factors in prevention of relapse of GPA is following up of patients by careful immunosuppressive dose adjustment and regular measurement of biomarkers for vasculitis. Herein, we describe an interesting case of biopsy-proven GPA who had a complex long history of several post-transplantation relapses in different organs with anti-neutrophil cytoplasmic antibodies seroconversion. This case emphasizes that vasculitis in particular GPA can mimic various diseases depending on which vessels and organs are affected by the inflammation and is one of the reversible causes of failure of transplanted kidney. Bearing the diagnosis in mind as one of the potential differential diagnoses of failure of renal transplantation will lead to early diagnosis and treatment of recurrent GPA.